The Development of an e-Traceability System for Cattle Delivery Chains - Seminar, Kudang Boro; Aditya, Edit Lesa; Imantho, Harry; Purnama, Diki Gita; Yani, Ahmad; Cyrilla, Lucia (International Journal of Supply Chain Management, 2020)
Transparency of livestock supply chain management is still a significant problem in Indonesia due to the unavailability of data and information accessible by the stakeholders of cattle supply chains. It is difficult to obtain information for queries, monitoring, and control purposes at any node along cattle supply chains, and thus introducing some risks of insecurity and uncertainty of cattle conditions along the supply chains. Nowadays, consumers are getting smarter and more curious about selecting healthy and high-quality beef. This requires the provision of an easily and securely accessible traceability and transparency system. The aim of this research is to develop an e-traceability system for cattle supply chains. The proposed e-traceability system was developed on the basis of a web-platform that provides wide access and easy links to all actors within a cattle supply chain and stakeholders. All actors in the cattle supply chain need to be registered and the data related to cattles need to be recorded in the traceability system database for analytic and decision-making. The potential applicability of the developed e-traceability system are examined and demonstrated to highlight the benefits of the system in improving transparency and traceability cattle deliveries from land to table for better managerial tasks.